Population of Merging Compact Binaries Inferred Using Gravitational Waves through GWTC-3 - R. Abbott; T. D. Abbott; F. Acernese; K. Ackley; C. Adams; N. Adhikari; R. X. Adhikari; V. B. Adya; C. Affeldt; D. Agarwal; M. Agathos; K. Agatsuma; et al. (Physical Review X, 2023)
We report on the population properties of compact binary mergers inferred from gravitational-wave observations of these systems during the first three LIGO-Virgo observing runs. The Gravitational-Wave Transient Catalog 3 (GWTC-3) contains signals consistent with three classes of binary mergers: binary black hole, binary neutron star, and neutron star–black hole mergers. We infer the binary neutron star merger rate to be between 10 and 1700  Gpc^{−3} yr^{−1} and the neutron star–black hole merger rate to be between 7.8 and 140  Gpc^{−3} yr^{−1}, assuming a constant rate density in the comoving frame and taking the union of 90% credible intervals for methods used in this work. We infer the binary black hole merger rate, allowing for evolution with redshift, to be between 17.9 and 44  Gpc^{-3} yr^{-1} at a fiducial redshift (z=0.2). The rate of binary black hole mergers is observed to increase with redshift at a rate proportional to (1+z)^{κ} with κ=2.9_{-1.8}^{+1.7} for z≲1. Using both binary neutron star and neutron star–black hole binaries, we obtain a broad, relatively flat neutron star mass distribution extending from 1.2_{-0.2}^{+0.1} to 2.0_{-0.3}^{+0.3}M_{⊙}. We confidently determine that the merger rate as a function of mass sharply declines after the expected maximum neutron star mass, but cannot yet confirm or rule out the existence of a lower mass gap between neutron stars and black holes. We also find the binary black hole mass distribution has localized over- and underdensities relative to a power-law distribution, with peaks emerging at chirp masses of 8.3_{-0.5}^{+0.3} and 27.9_{-1.8}^{+1.9}M_{⊙}. While we continue to find that the mass distribution of a binary’s more massive component strongly decreases as a function of primary mass, we observe no evidence of a strongly suppressed merger rate above approximately 60M_{⊙}, which would indicate the presence of a upper mass gap. Observed black hole spins are small, with half of spin magnitudes below χ_{i}≈0.25. While the majority of spins are preferentially aligned with the orbital angular momentum, we infer evidence of antialigned spins among the binary population. We observe an increase in spin magnitude for systems with more unequal-mass ratio. We also observe evidence of misalignment of spins relative to the orbital angular momentum.